Low Tidal Volume Ventilation during Cardiopulmonary Bypass Reduces Postoperative Chemokine Serum Concentrations - Beer, Lucian; Szerafin, Tamás; Mitterbauer, Andreas; Debreceni, Tamás; Maros, Tamás; Dworschak, Martin; Roth, Georg A.; Ankersmit, Hendrik Jan (The Thoracic and Cardiovascular Surgeon, 2014)
Background Open-heart surgery with cardiopulmonary bypass (CPB) is associated with a generalized immune response and postoperative lung dysfunction. Chemokines are involved in the pathogenesis of postoperative lung dysfunction. We investigated whether continued mechanical ventilation during CPB has an impact on chemokine serum concentrations.Methods A total of 30 patients undergoing coronary artery bypass graft operation were randomized to either continuous ventilated group (n = 15) or nonventilated group (n = 15). Blood samples were drawn at the beginning and at the end of surgery and on the 5 consecutive days. Serum CCL2, CCL4, and CCL20 concentrations were measured and given as mean ± standard deviation.Results Chemokine concentrations were elevated at the end of surgery in both groups. CCL2 and CCL4 levels returned to baseline on postoperative day (POD)-1 in the ventilation group and stayed elevated in the nonventilation group. CCL4 serum levels were significantly lower in ventilated-group patients on POD-1 (10.9 [39.0] vs. 153.2 [168.1]; p = 0.005), POD-2 (16.8 [36.8] vs. 147.9 [165.4]; p = 0.019), POD-3 (14.2 [24.0] vs. 97.9 [87.1]; p = 0.005), and POD-5 (6.5 [25.0] vs. 33.6 [38.4]; p = 0.045).Conclusion Continued mechanical ventilation during CPB results in reduced CCL4 concentrations on POD-1 to -5.
Keywords: cardiopulmonary bypass; CCL2; CCL4; CCL20; systemic inflammatory response syndrome; ventilation